PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN PELECEHAN SEKSUAL DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Diva Beauty Tomanda; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Everyone has human rights, one of which is legal protection. Victimprotection revealed that in principle it has been regulated in Law Section Number12 of 2022 concerning Crimes of Sexual Violence in articles 42 to article 47concerning Victim Protection. In accordance with the provisions of Article 4 ofthe Witness and Victim Protection Law, witness and victim protection aims toprovide a sense of security to witnesses and/or victims in providing informationduring any criminal detention process. Therefore, the aim of this thesis researchis firstly to explain the legal protection for female victims of sexual disclosurefrom the perspective of Indonesian criminal law, secondly to describe theweaknesses contained in the PSK Law regarding the legal protection of femalevictims of sexual disclosure.This research is normative legal research, referring to positive legalnorms that apply in Indonesia to answer issues that exist on the surface. This isbased on library research which takes quotations from book readings, orscientific research as support that is related to the problem to be researched. Thisresearch uses secondary data sources consisting of primary, secondary andtertiary legal materials. This research also uses qualitative data analysis andproduces descriptive data.From the results of the discussion it was concluded that, firstly, legalprotection for women who are sexually victims is discussed in the Criminal Lawin Indonesia regarding the restoration of victims' rights, while technicalprotection is mandated by the Witness and Victim Protection Law. The secondobstacle in legal protection for victims of sexual disclosure is that the realizationof the LPSK's duties and authority in the PSK Law is not specifically regulated ina separate provision or chapter, the victim is actually re-criminalized by theperpetrator through the ITE Law in the article on defamation, a culture ofblaming the victim, legal sanctions are required. For perpetrators of restitutiveviolence, many forms are open but the laws used are still the same, resulting inlegal violations. The author's suggestion is that regulations are needed thataccommodate a sense of justice for victims of sexual harassment. It requires astrong desire by each stakeholder to ensure that all stages run correctly.Keywords: Legal Protection, Victims, Sexual Harassment